Development Of Religious Character And Social Care In Elementary Schools - Bunsarpi Malina; Rahmi Novalita; Hariki Fitrah (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This study aims to explore the development of religious character and social care at SD Negeri 4 Kebayakan, Kebayakan District, Bireuen Regency. This type of research is qualitative research. The informants of this study are teachers of SD Negeri 4 Kebayakan, Central Aceh Regency. The informant selection technique uses the snowball sampling technique. Data collection techniques use observation, interviews and documentation. Data validity techniques use credibility, transferability, dependability, confirmability. Data analysis techniques use data reduction, data display, data interpretation, and drawing conclusions. The results of the study show that; 1) The development of religious character at SD Negeri 4 Kebayakan has various programs to develop students' religious character, such as instilling religious values ​​in the curriculum, congregational prayer, praying, reading Asmaul Husna, reading the Qur'an, tahfidz activities, charity, and short boarding schools. These programs aim to form students who are faithful, have noble character, and have a strong religious character. 2) The development of socially caring character at SD Negeri 4 Kebayakan through various programs such as the habit of sharing and empathy in daily activities, social activities such as community service and donations for disaster victims, the integration of caring values ​​into the curriculum and extracurricular activities, as well as the Friday Sharing program and mutual cooperation to clean the school environment. Through these programs, the school strives to instill the values ​​of caring and empathy in students, so that they grow into individuals who care about the environment and others.